A combined experimental and computational study of mechanical properties after balloon kyphoplasty. (August 2021) - Purcell, Philip; McEvoy, Fiona; Tiernan, Stephen; Sweeney, Derek; Morris, Seamus
Vertebral compression fractures rank among the most frequent injuries to the musculoskeletal system, with more than 1 million fractures per annum worldwide. The past decade has seen a considerable increase in the utilisation of surgical procedures such as balloon kyphoplasty to treat these injuries. While many kyphoplasty studies have examined the risk of damage to adjacent vertebra after treatment, recent case reports have also emerged to indicate the potential for the treated vertebra itself to re-collapse after surgery. The following study presents a combined experimental and computational study of balloon kyphoplasty which aims to establish a methodology capable of evaluating these cases of vertebral re-collapse. Results from both the experimental tests and computational models showed significant increases in strength and stiffness after treatment, by factors ranging from 1.44 to 1.93, respectively. Fatigue tests on treated specimens showed a 37% drop in the rate of stiffness loss compared to the untreated baseline case. Further analysis of the computational models concluded that inhibited PMMA interdigitation at the interface during kyphoplasty could reverse improvements in strength and stiffness that could otherwise be gained by the treatment.